Large-scale curriculum reform in Finland – exploring the interrelation between implementation strategy, the function of the reform, and curriculum coherence. Issue 1 (2nd January 2017) - Pietarinen, Janne; Pyhältö, Kirsi; Soini, Tiina
ABSTRACT: The study aims to gain a better understanding of the national large-scale curriculum process in terms of the used implementation strategies, the function of the reform, and the curriculum coherence perceived by the stakeholders accountable in constructing the national core curriculum in Finland. A large body of school reform literature has shown that a central determinant for the effectiveness of curriculum reform is the way in which the reform is implemented. Accordingly, implementing curriculum reform always entails translation of the new ideas into new educational practices, which involves complex sense-making processes from those involved. Altogether, 117 stakeholders accountable in constructing the national core curriculum in Finland completed a survey. The results showed that the effect of the implementation strategy for the perceived curriculum coherence was mediated by the perceived educational impact of the reform both for the school and society. The mediated interrelation between the top-down–bottom-up implementation strategy in the curriculum process, and the estimated coherence in the written core curriculum implies that the objects of the activities, namely elaborating and focusing on the educational impact of the decisions, is a crucial determinant for achieving curriculum coherence, and further, facilitating sustainable school development at the local level.